Timber Inventory: a primer for landowners - John Dooner; Michael G Andreu (EDIS, 2020)
This 7-page fact sheet written by John Dooner and Michael Andreu and published by the UF/IFAS School of Forest Resources and Conservation outlines a process called timber cruising, surveying timber inventory to estimate the current volume and value of a timber stand. The authors explain the process of timber cruising from initial tree-level measurements to the final total stand-level estimates and various methods for conducting the cruise. https://edis.ifas.ufl.edu/fr426